Pentingnya Keterampilan Sosial Dalam Berkomunikasi Melalui Nilai Karakter Sopan Santun - Anggie Rossana Indrayana,; Rahma Aprilia,; Mina Holilah,; Diana Noor Anggraini, (The Indonesian Journal of Social Studies, 2023)
Communication is an integral part of human life that allows the exchange of information, ideas and feelings between individuals. Social skills in communication have a major role in forming effective and meaningful interactions. In these situations, the use of polite words such as apologize, please, and thank you has proven to be an important element in creating healthy and harmonious social relations. This study aims to determine how far social skills are in communicating through polite characters, namely the use of the words sorry, please, and thank you. The research approach used was qualitative with descriptive methods. Data collection techniques used observation and questionnaires as data collection instruments. Observation and questionnaire data analysis techniques and research subjects were active students of Social Studies Education at the Indonesian University of Education. The results of the study show that the character of politeness plays an important role in communicating with someone. In addition, politeness also makes a significant contribution in building empathy and solidarity between individuals. On the other hand, the use of the word thank you is considered as an expression of respect and appreciation for the efforts or assistance provided by others. This article provides further understanding of how important social skills are in communicating through the character of courtesy. The implications of this research can inspire individuals to pay more attention to the importance of social skills in everyday interactions.